Assessment of information as regards the toxicity of deoxynivalenol for horses and poultry. (2nd February 2023) - ,; Schrenk, Dieter; Bignami, Margherita; Bodin, Laurent; del Mazo, James Kevin Chipman Jesús; Grasl‐Kraupp, Bettina; Hogstrand, Christer; Leblanc, Jean‐Charles; Nielsen, Elsa; Ntzani, Evangelia; Petersen, Annette; Sand, Salomon; et al.
Abstract: In 2017, the EFSA Panel on Contaminants in the Food Chain (CONTAM) adopted a Scientific Opinion on the risks for animal health related to the presence of deoxynivalenol (DON) and its acetylated and modified forms in food and feed. No observed adverse effect levels (NOAELs) and lowest observed adverse effect levels (LOAELs) were derived for different animal species. For horses, an NOAEL of 36 mg DON/kg feed was established, the highest concentration tested and not showing adverse effects. For poultry, an NOAEL of 5 mg DON/kg feed for broiler chickens and laying hens, and an NOAEL of 7 mg DON/kg feed for ducks and turkeys was derived. The European Commission requested EFSA to review the information regarding the toxicity of DON for horses and poultry and to revise, if necessary, the established reference points (RPs). Adverse effect levels of 1.9 and 1.7 mg DON/kg feed for, respectively, broiler chickens and turkeys were derived from reassessment of existing studies and newly available literature, showing that DON causes effects on the intestines, in particular the jejunum, with a decreased villus height but also histological damage. An RP for adverse animal health effects of 0.6 mg/kg feed for broiler chickens and turkeys, respectively, was established. For horses, an adverse effect level of 5.6 mg DON/kg feed was established from studies showing reduced feed intake, with an RP for adverse animal health effects of 3.5 mg/kg feed. For ducks and laying hens, RPs remain unchanged. Based on mean and P95 (UB) exposure estimates performed in the previous Opinion, the risk of adverse health effects of feeds containing DON was considered a potential concern for broiler chickens and turkeys. For horses, the risk for adverse health effects from feed containing DON is low.